Integrating Technology in Language Education: A Critical Review of Current Practices and Future Trends - Rani Ligar Fitriani; Rudi hartono; Sri Wahyuni (Institut Agama Islam Negeri Palopo, 2025)
The integration of Information Technology (IT) into language instruction has transformed traditional teaching methodologies by providing learners with more interactive, personalized, and accessible learning experiences. This study examines the impact of IT tools, such as Computer-Assisted Language Learning (CALL) and Mobile-Assisted Language Learning (MALL), on language acquisition, learner engagement, and motivation. A systematic review of 25 studies published between 2015 and 2025 was conducted to explore the use of these tools in language education. The findings suggest that IT-based tools significantly enhance learners' vocabulary acquisition, listening comprehension, and speaking proficiency. Mobile applications and online platforms foster greater learner engagement through gamification, immediate feedback, and self-paced learning opportunities. However, the study also highlights challenges such as technological limitations, the need for instructor training, and concerns about over-reliance on digital tools. While IT tools provide valuable support in language learning, a balanced approach that combines traditional methods with technology is recommended to optimize educational outcomes. These findings contribute to understanding the potential of IT in language instruction and suggest directions for future research on improving the integration of technology in educational contexts.